Analysis Of The Social And Cultural Values Contraining Increased African Apple Production In Anambra State Of Nigeria - Enibe, D. O. (Advances in Social Sciences Research Journal, 2020)
This study analysed the social and cultural values constraining increased African Star Apple (ASA, Chrysophilum albidum) production in Anambra State of Nigeria. Data were collected using interview schedule on 80 respondents selected from six major assembly markets in six town communities of two Agricultural zones of the State. Ten respondents (5 men and 5 women) who are natives of the communities hosting the markets were selected through Snow ball sampling method (SBSM) from each of the markets. The interview schedule was mainly on yes or no questions. From the respondents, 7 in-depth interviews were conducted for detailed information on ASA important issues such as the crop’s feast activities, children’s song while under the trees and beliefs. Data were achieved with descriptive statistics such as percentage, frequency distribution and Tables. The study showed that: ASA production and consumption in the study area are by 100% constrained with social and cultural norms such as none planting, none harvesting, public ownership and free fruits collection. The result also reveals that the studied communities differ in their ASA fruit selling and buying norms and in ASA feast in the past and that they do not easily change their norms except on certain conditions such as knowledge gain and sensitization. The study inter alia recommends that effort to increase or commercialize its production by entrepreneurs requires orientation or sensitization of the tradition custodians in the communities and adequate protection of the trees in farm fields or plantations.